1996
DOI: 10.1007/bf01291787
|View full text |Cite
|
Sign up to set email alerts
|

Neuropharmacological characterization of local ibogaine effects on dopamine release

Abstract: Local perfusion with ibogaine (10(-6) M-10(-3) M) via microdialysis probes in the nucleus accumbens or striatum of rats produced a biphasic dose-response effect on extracellular dopamine levels. Lower doses (10(-6) M-10(-4) M) produced a decrease while higher doses (5 x 10(-4) M-10(-3) M) produced an increase in dopamine levels. Dihydroxyphenylacetic acid (DOPAC) levels were not effected. Naloxone (10(-6) M) and norbinaltorphimine (10(-6) M-10(-5) M) did not affect dopamine levels, but when co-administered wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…However, this compound is also a reversible monoamine oxidase-A (MAO-A) inhibitor, which itself and by its metabolite harmine, enhances dopaminergic transmission in the striatum [17,[33][34][35]. The present results showing that dopaminergic receptor stimulation enhances tremor induced by this agent, suggest that the above striatal mechanism may contribute to this behavior.…”
Section: Discussionmentioning
confidence: 46%
“…However, this compound is also a reversible monoamine oxidase-A (MAO-A) inhibitor, which itself and by its metabolite harmine, enhances dopaminergic transmission in the striatum [17,[33][34][35]. The present results showing that dopaminergic receptor stimulation enhances tremor induced by this agent, suggest that the above striatal mechanism may contribute to this behavior.…”
Section: Discussionmentioning
confidence: 46%
“…These competitive inhibitors include several compounds that also inhibit the closely related dopamine and norepinephrine transporters (17, 29). Previous reports suggested that both SERT and DAT were sensitive to inhibition by ibogaine (5, 30). Therefore, we compared the kinetics of ibogaine inhibition of SERT and DAT.…”
Section: Resultsmentioning
confidence: 92%
“…Activity against MAO-B is negligible 94. Harmaline inhibits synaptosomal GABA uptake (IC 50 47 μM)95 and dopamine uptake (IC 50  = 8.1 μM),96 and increases dopamine release from striatal slices at 6 μM 94. Low doses enhance levodopa-induced stereotypy in mice 97.…”
Section: Resultsmentioning
confidence: 99%